Ḥakīm Āgẖā Jān ʻAish aur Haryānah ke mashāhīr - Ma̤tīr, Baljīt Singh (Dihlī kī navāḥī bastiyoṉ meṉ Urdū ; jild 1., 1981)
Brief biographies and poems of early Urdu poets from Haryana with special reference to Āghā Jān ʻAish, 19th century.